The Role of Teacher Mindfulness in Managing Students’ Emotions in SBdP Learning at SD Inpres 1 Talise - Ira Ira; Andi Imrah Dewi; Kadek Hariana; Zulnuraini Zulnuraini; Andi Rahmaeni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The background of this research is based on the importance of developing students’ emotional regulation skills from an early age, as well as the teacher’s role in creating a calm, focused, and mindful learning environment. Effective emotional management is expected to help students interact, learn, and adapt better to the school environment. This study aims to describe the role of teacher mindfulness in managing second-grade students' emotions during SBdP (Arts, Culture, and Crafts) lessons at SD Inpres 1 Talise. This study employs a qualitative approach with a descriptive research design. The research subjects consist of second-grade teachers and students. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data display, and conclusion drawing. The results indicate that teacher mindfulness is reflected in calm, patient teaching behavior, gentle communication, and the consistent ability to provide students with attention and appreciation. Teachers are also able to regulate their emotions effectively when facing various classroom situations, such as noisy students, conflicts over materials, or students feeling disappointed with their work. The implementation of mindfulness has a positive impact on students’ emotional management, as shown by increased patience, reduced anger, improved self-confidence, better cooperation, and greater focus. Additionally, students appear more engaged, actively participate, and enjoy the SBdP learning process in the classroom overall. Teacher mindfulness has a positive and significant role in improving students’ emotional management and creating a more engaging learning environment.